2010
DOI: 10.1088/0004-637x/723/1/492
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties and Galactic Distribution of Molecular Clouds Identified in the Galactic Ring Survey

Abstract: We derive the physical properties of 580 molecular clouds based on their 12 CO and 13 CO line emission detected in the University of Massachusetts-Stony Brook (UMSB) and Galactic Ring surveys. We provide a range of values of the physical properties of molecular clouds, and find a power-law correlation between their radii and masses, suggesting that the fractal dimension of the ISM is around 2.36. This relation, M = (228±18) R 2.36±0.04 , allows us to derive masses for an additional 170 GRS molecular clouds not… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

91
447
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(545 citation statements)
references
References 72 publications
(146 reference statements)
91
447
7
Order By: Relevance
“…This arm is prominent in CO (3-2) and therefore has abundant molecular gas content at these longitudes . It is also a strong feature in the RMS source distribution (Urquhart et al 2014a), gas temperature (Roman-Duval et al 2010), and the ratio of infrared luminosity to clump mass (LIR/M clump Moore et al 2012;Eden et al 2015) suggestive of enhancement in the SFE, albeit on the kiloparsec scales probed by earlier surveys. This, however, may be a consequence of local variations (e.g.…”
Section: What Does the Star-forming Fraction (Sff) Mean?mentioning
confidence: 93%
“…This arm is prominent in CO (3-2) and therefore has abundant molecular gas content at these longitudes . It is also a strong feature in the RMS source distribution (Urquhart et al 2014a), gas temperature (Roman-Duval et al 2010), and the ratio of infrared luminosity to clump mass (LIR/M clump Moore et al 2012;Eden et al 2015) suggestive of enhancement in the SFE, albeit on the kiloparsec scales probed by earlier surveys. This, however, may be a consequence of local variations (e.g.…”
Section: What Does the Star-forming Fraction (Sff) Mean?mentioning
confidence: 93%
“…Note also that the GMCs are somewhat confined by the pressure of the ambient, uniform density medium. Observed GMCs appear to have smaller virial parameters, ∼1 (e.g., Roman-Duval et al 2010;Kauffmann et al 2013), especially when considering their positionvelocity connected, 13 CO-emitting structures (Hernandez & Tan 2015). Our choice of initializing with a larger kinetic energy content is motivated by the desire to not have rapid global collapse of the clouds within the first few megayears, i.e., the timescale of the collision.…”
Section: Initial Conditionsmentioning
confidence: 99%
“…Roman-Duval et al (2010) found M ∝ r 2.26 for molecular clouds having sizes in the range 0.7−30 pc. Heithausen et al (1998) found M ∝ r 2.31 for scales ranging from 0.01 to 1 pc.…”
Section: Massmentioning
confidence: 97%
“…In other words, the mass does not scale with L 3 (see Fig. 8), therefore the density estimated over large physical scales is an underestimate of the density at small scales, explaining why the average density in GMCs is found to be smaller than the critical density of CO. For instance, from the sample of molecular clouds of Roman-Duval et al (2010), one obtains that n H2 = 800L −0.64 . For the typical size of a structure in Draco (L = 0.15 pc, see Fig.…”
Section: Gas Densitymentioning
confidence: 99%